PENGARUH PENGGUNAAN MEDIA OBJEK LANGSUNG TERHADAP KETERAMPILAN MENULIS TEKS LAPORAN OBSERVASI SISWA KELAS VII SMP NEGERI 2 LINGGO SARI BAGANTI KABUPATEN PESISIR SELATAN - Marpianti, Resni; Atmazaki, Atmazaki; Noveria, Ena (Universitas Negeri Padang, 2016)
ABSTRACT The purpose of this study to describe three things. First, the text of the report writing skills on the observation class VII SMP 2 Linggo Sari Baganti South Coastal District without using media direct object. Second, the text of the report writing skills on the observation class VII SMP 2 Linggo Sari Baganti South Coastal District using media direct object. Third, the effect of the application object media directly to the learning skills of writing text of the report on the observation of students of class VII SMP 2 Linggo Sari Baganti South Coastal District. This research is a quantitative experimental methods and research design static two groups (the experimental class and control class). Based on the results of the study concluded the following three things. First, the text of the report writing skills on the observation without using the media direct object class VII SMP 2 Linggo Sari Baganti South Coastal District are in qualification More than Just an average of 66.11. Second, the text of the report writing skills of observation results by using the media direct object class VII SMP 2 Linggo Sari Baganti South Coastal District are in the qualification Good with the average value of 78.84. Third, based on the t-test results, it was concluded that there is a direct influence of the media object to the text of the report writing skills on the observation class VII SMP 2 Linggo Sari Baganti South Coastal District for tcount> ttable (4.30> 1.68). In other words, media direct object is best applied in the process of learning the skills to write text report the observation of students of class VII SMP 2 Linggo Sari Baganti South Coastal Distric. Kata kunci: Pengaruh, Media Objek Langsung, Menulis, Teks Laporan Hasil Observasi